2021
DOI: 10.3390/molecules26123484
|View full text |Cite
|
Sign up to set email alerts
|

Complexes with Atomic Gold Ions: Efficient Bis-Ligand Formation

Abstract: Complexes of atomic gold with a variety of ligands have been formed by passing helium nanodroplets (HNDs) through two pickup cells containing gold vapor and the vapor of another dopant, namely a rare gas, a diatomic molecule (H2, N2, O2, I2, P2), or various polyatomic molecules (H2O, CO2, SF6, C6H6, adamantane, imidazole, dicyclopentadiene, and fullerene). The doped HNDs were irradiated by electrons; ensuing cations were identified in a high-resolution mass spectrometer. Anions were detected for benzene, dicyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 71 publications
(102 reference statements)
2
6
0
Order By: Relevance
“…They also note satisfactory agreement with the earlier computational predictions of Bauschlicher et al for Cu + (214 ± 21 kJ mol –1 ) and Ag + (153 ± 21 kJ mol –1 ) and the experimental CID results for Cu + / C 6 H 6 : 218 ± 10 kJ mol –1 reported by Armentrout et al and 209 ± 38 kJ mol –1 reported by Hetrich and Freiser . Also, in the case of gold, their computed value agrees with the estimate of 280 ± 29 kJ mol –1 reported by Schröder et al However, the computed value of 179 kJ mol –1 for the binding energy of the gold cation to benzene reported very recently by Duensing et al is much lower. These authors also reported a binding energy of 242 kJ mol –1 for the second benzene in the formation of the bis-adduct in which the gold cation forms covalent bonds over two adjacent carbon atoms in each ring.…”
Section: Results and Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…They also note satisfactory agreement with the earlier computational predictions of Bauschlicher et al for Cu + (214 ± 21 kJ mol –1 ) and Ag + (153 ± 21 kJ mol –1 ) and the experimental CID results for Cu + / C 6 H 6 : 218 ± 10 kJ mol –1 reported by Armentrout et al and 209 ± 38 kJ mol –1 reported by Hetrich and Freiser . Also, in the case of gold, their computed value agrees with the estimate of 280 ± 29 kJ mol –1 reported by Schröder et al However, the computed value of 179 kJ mol –1 for the binding energy of the gold cation to benzene reported very recently by Duensing et al is much lower. These authors also reported a binding energy of 242 kJ mol –1 for the second benzene in the formation of the bis-adduct in which the gold cation forms covalent bonds over two adjacent carbon atoms in each ring.…”
Section: Results and Discussionsupporting
confidence: 87%
“…Table provides a summary of our calculated ligation enthalpies at 298 K. We have included the recent computed value by Duensing et al for the bis-adduct of Au + and benzene for which our calculations did not converge.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cluster formation of adamantane cations within helium droplets has been explored previously by our group, [49][50][51] employing time-of-flight mass spectrometry. Fig.…”
Section: Resultsmentioning
confidence: 99%